Management of acute diarrhoeal disease at Edendale Hospital: Are standard treatment guidelines followed? - Kershinee Reddy; M E Patrik; C R Stephen (South African Medical Association, 2016)
Background. Diarrhoeal disease (DD) is a major cause of childhood mortality in developing countries. In South Africa (SA), it ranks as one of the top five causes of under-5 mortality. Local and global guidelines on the management of acute DD are readily available. The Standard Treatment Guidelines (STGs) and Essential Drugs List for Hospital Level Paediatrics are a recognised standard of care for children in SA hospitals. However, children still die from this preventable disease. Objective. To determine whether doctors adhered to standard treatment guidelines when treating children under 5 years of age presenting to Edendale Hospital in Pietermaritzburg, KwaZulu-Natal Province, with acute DD. Methods. The study was a retrospective clinical audit of individual patient records. Results. One hundred and thirty-five patient records were reviewed. Forty-seven percent had a correct nutritional assessment, 41% were correctly assessed for shock and 27% for dehydration. Appropriate investigations were undertaken in 12%. Ninety-seven percent of patients had appropriate fluid plans prescribed. Zinc was prescribed in only 39% of patients, whereas 84% were appropriately not prescribed antibiotics and no patients received anti-diarrhoeal medication. In 90% of patients, the correct post-care patient referral was made, and 47% of caregivers were adequately advised about ongoing care of their children. Conclusion. This study identifies substantial non-adherence to the SA STGs for the management of young children with acute DD.